Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1074/jbc.m109.015446
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Mouse Mast Cell Protease-2 by Interleukin-15

Abstract: Mast cells (MCs) play a critical role in innate and adaptive immunity through the release of cytokines, chemokines, lipid mediators, biogenic amines, and proteases. We recently showed that the activities of MC proteases are transcriptionally regulated by intracellularly retained interleukin-15 (IL-15), and we provided evidence that this cytokine acts as a specific regulator of mouse mast cell protease-2 (mMCP-2). Here, we show that in wild-type bone marrow-derived mast cells (BMMCs) IL-15 inhibits mMCP-2 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
0
12
1
Order By: Relevance
“…Mcpt-2 promoter activity [17]. In addition, the percentage of the FceRI + c-kit + cell population and the level of FceRI and c-kit expression were not altered by C/EBPa-knockdown or overexpression in our experiments, while Xi et al indicated that basophils converted into mast cells under C/EBPa knockdown condition using C/EBPa conditional knockout mice [16].…”
Section: C/ebpa Suppresses Granule Formation In Mast Cellscontrasting
confidence: 43%
“…Mcpt-2 promoter activity [17]. In addition, the percentage of the FceRI + c-kit + cell population and the level of FceRI and c-kit expression were not altered by C/EBPa-knockdown or overexpression in our experiments, while Xi et al indicated that basophils converted into mast cells under C/EBPa knockdown condition using C/EBPa conditional knockout mice [16].…”
Section: C/ebpa Suppresses Granule Formation In Mast Cellscontrasting
confidence: 43%
“…These players prominently include the following; CTLA‐4, an important T‐cell immunoinhibitory surface molecule, CTLA4 ligands CD80 and CD86, 297‐299 and IL‐15, 42,106,300 a key immunostimulatory cytokine that drives NK/NKT cell development and survival. IL‐15 is also is a key mast cell regulator and effector 301‐304 …”
Section: Hair Follicle Immune Privilege Collapse As a Prerequisite Fomentioning
confidence: 99%
“…Protease activity is tightly regulated at a minimum of four levels, which include transcriptional regulation, post-translational modification, physical compartmentalization and functional inhibition (Chow et al 1995; Gorogh et al 2006; Lopez-Otin and Matrisian 2007; Mirghomizadeh et al 2009; Muzio et al 1997). The multiple levels of protease regulation provide for tight tissue, temporal and environmentally responsive control of activity.…”
Section: Protease Regulationmentioning
confidence: 99%